Non-contrast mastoid CT scan technique in Chronic Suppurative Otitis Media (CSOM) at radiology department of PMI Bogor Hospital - Khayla Rafina Niradita; Nursama Heru Apriantoro; Khairil Anwar (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2026)
Chronic Suppurative Otitis Media (CSOM) is a persistent inflammation of the middle ear that requires precise radiological evaluation to prevent severe complications. Non-contrast High-Resolution Computed Tomography (HRCT) of the mastoid is the gold standard for assessing temporal bone anatomy. This study aimed to describe the technical procedure of non-contrast mastoid CT scans for CSOM clinical cases at PMI Bogor Hospital. The method used was a descriptive qualitative study with a case study approach on a pediatric patient. Data were collected through observation of scanning parameters and image reconstruction techniques. The results showed that the examination was performed using multiple reconstruction planes. Analysis of different slice thicknesses revealed that 1 mm axial slices provided superior spatial resolution for visualizing the ossicular chain and mastoid air cells compared to 3 mm slices. Radiological findings confirmed normal mastoid pneumatization and intact ossicles, effectively excluding complications despite clinical symptoms. In conclusion, the implementation of thin-slice reconstruction at PMI Bogor Hospital is essential for high diagnostic confidence. This technical approach ensures an accurate "map" of the temporal bone, which is vital for clinical management and surgical planning.